Performance tuning of scientific applications - Bailey, David H.; Lucas, Robert F.; Williams, Samuel Watkins (Boca Raton, FL : CRC Press, 2011)
'This book presents an overview of recent research and applications in computer system performance for scientific and high performance computing. After a brief introduction to the field of scientific computer performance, the text provides comprehensive coverage of performance measurement and tools, performance modeling, and automatic performance tuning. It also includes performance tools and techniques for real-world scientific applications. Various chapters address such topics as performance benchmarks, hardware performance counters, the PMaC modeling system, source code-based performance modeling, climate modeling codes, automatic tuning with ATLAS, and much more'--
Includes bibliographical references and index.
Keywords: Science -- Data processing -- Evaluation; Electronic digital computers -- Evaluation; System design -- Evaluation; Science -- Computer programs